Strategi Komunikasi Interpersonal KH. Agus Maulana dalam Menanamkan Kreativitas - Rivaldo, Rivaldo; As’ad , Muhamad (ILJ: Islamic Learning Journal, 2025)
Islamic boarding schools are Islamic educational institutions that play an important role in shaping the character, morals, and skills of students. In the midst of the challenges of the modern era, pesantren are required not only to teach religious knowledge, but also to equip students with the ability to face changing times, including in terms of developing creativity. This study aims to determine the interpersonal communication strategy applied by KH Agus Maulana in instilling creativity values to students at Al-Muhsinin Islamic Boarding School. Descriptive qualitative research method. Collection techniques through observation, interviews, and documentation. The results showed that the interpersonal communication carried out by KH Agus Maulana was personal, dialogical, and participatory. Through this approach, santri are encouraged to think creatively, be open to new ideas, and be active in various activities in the pesantren environment.